(untitled) (Swiss Medical Weekly, 2026)
This article presents a comprehensive overview of perioperative pain medicine based on recently published recommendations by the Swiss Society of Anaesthesiology and Perioperative Medicine (SSAPM). As it has long been known that improvements in postoperative pain management depend more on organisational structures than on new drugs or techniques, these recommendations focus on the structures and processes of perioperative pain management. The introduction of Acute Pain Services (APS) by anaesthesiology departments in the 1980s marked significant progress. However, APS coverage remains limited and inconsistent across institutions, often lacking sufficient resources. To address these gaps, the SSAPM convened a multiprofessional expert group to develop structural and procedural recommendations. Key structural recommendations emphasise the necessity of interdisciplinary and interprofessional collaboration, with jointly developed and signed protocols between surgical and pain services to clarify responsibilities and prevent care gaps. Hospitals are urged to maintain written, evidence-based standard procedures for multimodal pain management tailored to local conditions. The availability of qualified personnel for pain management is also a key recommendation. Process recommendations highlight the importance of multidisciplinary, multiprofessional approaches and seamless communication between personnel involved in perioperative care, patients, and external care providers. Preoperative patient education, the identification of individuals at risk for complex pain trajectories or chronic postsurgical pain (CPSP), and structured follow-up are essential components. The continuum of care from inpatient to outpatient settings is another key element. Overall, these recommendations aim to standardise and define perioperative pain management as a core element of modern perioperative medicine.